IMPLIKASI HUKUM PUTUSAN PAILIT TERHADAP JABATAN NOTARIS DAN AKTA YANG DI BUATNYA (Studi Putusan Nomor 20/Pdt.Sus-Pkpu/2020/Pn Niaga Sby) - Narenggar Daranindra Pasca Archqueta (Indonesian Journal of Islamic and Social Science, 2024)
Article 9 paragraph (1) letter a of Law No. 30 of 2004 combined with Law No. 2 of 2014 regarding the functions of notaries when the notary is temporarily dismissed due to “bankruptcy proceedings or postponement "obligation" repayment, according to this regulation, for a notary who is in bankruptcy proceedings or has delayed payments, that notary  will only be temporarily suspended  until there is a court decision. permanent legal effect. This study addresses the legal situation of a notary who was temporarily suspended by the MPD due to  bankruptcy proceedings and the effect of the statute brought by the notary in bankruptcy proceedings. The research method used is normative research, using a statutory approach, a conceptual approach and a case approach, using secondary data that will be analyzed using descriptive analysis. The results of this study are the legal status of notaries  temporarily suspended by the MPD due to  bankruptcy proceedings, unable to exercise their  notary rights, and the validity of documents drawn up by notaries during the process. Bankruptcy is not valid.